Examining the Relationship between Corporate Innovation and Firm Performance: Evidence from the UK and the U.S. - Ren, Nanwei
This paper serves to examine the impact of corporate innovation on firm performance. A series of multiple regression analyses are conducted on 300 companies in the United Kingdom (UK) and the United States (U.S.) from 2000-2019. The results reveal that, in most cases, there is no significant correlation between corporate innovation and firm performance. However, in some rare cases, a positive relationship between corporate innovation and firm performance is observed. It is consequently maintained that research and development (R&D) activities do not affect the profitability of enterprises. The significance of the study is that it shows that when companies continuously invest in R&D and innovation activities, this fails to affect their competitive advantages ultimately. Moreover, a series of comparative analysis of the results of high and low technology industries in the U.S. and the UK is conducted. It is established that the effects of corporate innovation in low-tech industries on corporate performance are more positive than that of high-tech industries.